CERVICAL CANCER PREVENTION KNOWLEDGE AND ATTITUDES AMONG FEMALE UNIVERSITY STUDENTS AND HOSPITAL STAFF IN IRAN: AN IN-DEPTH ANALYSIS - Kolkata , Singh; Ahmed, Pune . (Global Journal of Medical and Health Science, 2023)
Cervical cancer remains a global health challenge, with prevention through knowledge and positive attitudes playing a crucial role. This study presents an in-depth analysis of cervical cancer prevention knowledge and attitudes among female university students and hospital staff in Iran. Cervical cancer is a preventable disease, primarily through vaccination against high-risk Human papillomaviruses (HPV) and regular screening, such as the Papanicolaou (PAP) test. However, the success of prevention strategies relies heavily on individuals’ knowledge and attitudes towards these interventions. In this study, a comprehensive survey was conducted among female university students and hospital staff in Iran, aiming to assess their knowledge of cervical cancer, its risk factors, screening methods, and vaccination. Additionally, attitudes towards preventive measures, including HPV vaccination and PAP testing, were explored. The findings revealed a spectrum of knowledge levels among participants, with variations in awareness of risk factors and prevention methods. While some respondents demonstrated a solid understanding of cervical cancer prevention, others exhibited knowledge gaps, particularly concerning HPV vaccination. Attitudes towards preventive measures were generally positive, but barriers such as misconceptions, cultural factors, and access to healthcare services were identified as influencing factors. This in-depth analysis sheds light on the strengths and weaknesses of cervical cancer prevention knowledge and attitudes among female university students and hospital staff in Iran. It underscores the importance of tailored educational interventions to bridge knowledge gaps, dispel misconceptions, and promote positive attitudes towards HPV vaccination and PAP testing. Efforts to enhance awareness and foster a proactive approach to cervical cancer prevention are essential to reduce the burden of this disease in Iran. Public health initiatives should target both students and healthcare professionals, fostering a collective commitment to early detection and vaccination as cornerstones of cervical cancer prevention